Pengaruh Kesadaran, Pemahaman Dan Sanksi Terhadap Kepatuhan Wajib Pajak Reklame Di Kota Bekasi Tahun 2024 - Victor Yudistira Antoro; Hartono (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
Billboard Tax Compliance refers to the level of awareness, adherence, and compliance of individuals or business entities with tax obligations related to billboard installation in accordance with applicable regulations. Billboard tax is levied on advertising activities, typically including the placement of advertisements or promotional media in public spaces. The aim of this study is to analyze and measure the influence of taxpayer awareness, understanding, and sanctions on billboard tax compliance in the city of Bekasi. The research adopts a quantitative approach using a survey method with a simple random sampling technique. Data were collected from 100 respondents through questionnaires. Data analysis was performed using SPSS version 25.0. This study examines the relationship between independent variables (Awareness, Understanding, and Sanctions) and the dependent variable (Compliance) through hypothesis testing.The analysis prerequisites involve multiple linear regression to determine the degree of correlation (simultaneous) between two or more independent variables (X) and the dependent variable (Y). The findings of this study demonstrate a significant positive influence of taxpayer awareness, understanding, and sanctions on billboard tax compliance in Bekasi, both partially and simultaneously. Partial Analysis: Awareness (X1) has a significant positive effect on Compliance (Y) with a t-value of 1.890, which is less than the critical t-value (t-table, df=97) of 1.985.Understanding (X2) also has a significant positive effect on Compliance (Y), with a t-value of 1.090, which is less than the critical t-value (t-table, df=97) of 1.985. Sanctions (X3) have a significant positive effect on Compliance (Y), with a t-value of 0.770, which is less than the critical t-value (t-table, df=97) of 1.090. Simultaneous Analysis: It is concluded that Awareness (X1), Understanding (X2), and Sanctions (X3) collectively influence Compliance (Y) since the significance value is 0.00, which is less than 0.05, and the calculated F- value (F-Calculated) is 5069.186, which is greater than the critical F-value (F-Table) of 3.09.